Igraine the brave - Funke, Cornelia, 1958- (Chicken House/Scholastic, 2007)
The daughter of two magicians, twelve-year-old Igraine wants nothing more than to be a knight, and when their castle is attacked by a treacherous neighbor bent on stealing their singing magic books, Igraine has an opportunity to demonstrate her bravery.